Does telomerase activity have an effect on infertility in patients with endometriosis?. (June 2017) - Sofiyeva, Nigar; Ekizoglu, Seda; Gezer, Altay; Yilmaz, Handan; Kolomuc Gayretli, Tugba; Buyru, Nur; Oral, Engin
Abstract: Objective: This study aimed to investigate the role of telomerase activity in the development of endometriosis-related infertility by evaluation of the serum telomerase in eutopic and ectopic endometrial tissue. Study design: Eutopic endometrium, cystic wall/ovarian cortex, and venous blood were assessed in forty-seven patients. The following groups of patients were identified: females with endometriosis requiring surgical intervention and healthy control females. Patients with histopathologically confirmed endometriosis were further subdivided in the infertile (n = 14) and fertile (n = 17) groups. Patients who underwent hysterectomy and oophorectomy for benign gynecological conditions were enrolled in the healthy control group (n = 16). Telomerase activity was evaluated with three-group, endometriosis-based and fertility-based designs. Analyses were performed regardless the menstrual cycle phase (Phase G), in proliferative (Phase P) (n = 22) and secretory phases (Phase S) (n = 25). Telomeric Repeat Amplification Protocol PCR was applied for telomerase activity assessment. All statistical analyses were performed with STATA 14.2, GraphPad Prisma 7.01. Results: In analyses of the eutopic endometrium, with three-group design, a significant difference was not found in Phase G and P (p = 0.58 and p = 0.33, respectively). However, a statistical difference was shown in Phase S (p = 0.008). A significant difference was not established in Phase G, P and S of endometriosis-based design (p = 0.35, p = 1.0, p = 0.13, respectively). No difference was detected in Phase G and P of fertility-based design (p = 0.66 and p = 0.14, respectively), whereas in secretory phase difference was approved (p = 0, 049). Telomerase activity was not established in ectopic endometrium and in serum assessment. Conclusions: Telomerase activity is useless as a biomarker in peripheric blood analysis. The absence of activity in cystic wall approves the high differentiation of endometriosis tissue, what is the possible reason of low malignancy risk. The high rate of telomerase activity in the eutopic endometrium of the infertile group may be considered as a cause of endometriosis-related infertility.